Piston wind characteristic and energy saving of metro station environmental control system. (December 2021) - He, Deqiang; Teng, Xiaoliang; Chen, Yanjun; Yuan, Yuzhao; Li, Xianwang; Shan, Sheng
Abstract: Energy-saving is conductive to sustainable development. However, metro environmental control system accounts for great energy consumption in subway system. This paper focused on the effective utilization of unorganized fresh air induced by piston effect in the transitional season, aiming to save energy of ventilation system in metro station, and the method of combining numerical simulation with experiment was used. Firstly, the validity of numerical model was verified by comparing with experimental data. Secondly, the operation mode of environmental control system in metro station was reasonably scheduled, and the energy saving of ventilation system of metro station in the cities with different climate was calculated. The results show that the new environmental control system has the potential to save energy compared with traditional platform screen doors system. In some cities of temperate zone, the maximum energy saving is 75890 kW h of electricity every year. The maximum rate of energy saving is 42.71% with remarkable energy saving effect. The energy saving potential in other climates is limited, especially in cold zone, where the minimum energy saving is merely 23759 kW h of electricity every year, and the minimum rate of energy saving is only 9.67%. Besides, the results also indicate that unorganized fresh air flowing into the station is mainly caused by the suction effect of the moving train, which could be well applied to the design of environmental control system of metro station and provide a theoretical basis for utilization of unorganized fresh air induced by piston effect. Highlights: An energy-saving operation mode of environment control system of metro station is proposed. The new environmental control system has the potential to save electricity. A conclusion that the suction effect is stronger than the extrusion effect is reached. The suction effect results in unorganized fresh air flowing into station.